Rehabilitation possibilities for children with cerebral palsy through the use of robotic devices and biofeedback - N. V. Larina; V. B. Pavlenko; L. L. Korsunskaya; Yu. O. Dyagileva; A. P. Falaleev; A. A. Mikhailova; L. S. Orekhova; I. V. Ponomareva (Бюллетень сибирской медицины, 2020)
This article overviews and systemizes published data on the ways of implementing different methods of biofeedback, robotic devices, and brain-computer interfaces (BCI) for rehabilitation of children with cerebral palsy (CP).Aim. To survey implementation practices and clinical outcomes of rehabilitation technologies and possible neurophysiological mechanisms underlying their efficacy in patients with CP. We searched PubMed, Web of Science and eLIBRARY.ru databases for relevant publications using specified keywords.Results. The analysis of relevant literature has shown that robotic technologies and BCIs with biofeedback based on electroencephalography and electromyography parameters are rapidly developing and implemented for the rehabilitation of children with CP. The first evidence of effectiveness for such methods and approaches has been found. However, there is a lack of fully developed conventional standards for the use of such rehabilitation methods and protocols in children. Control groups comprising of children with CP are often absent in such studies. In many cases, the variations of neurophysiological and neurochemical parameters before and after a course of rehabilitation are not evaluated. Having such data would help clarify physiological mechanisms underlying effective rehabilitation of motor functions and then design more adequate rehabilitation procedures and medication protocols.